POLITIK HUKUM PEMBENTUKAN DESA ADAT DALAM SISTEM PEMERINTAHAN DI INDONESIA - Rauf, Muhammad A. (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
This study aims to determine the legal political formation of indigenous villages in the government system in Indonesia. Village administration system becomes an important issue in setting the model villages in Indonesia. State recognition of indigenous villages punctuated with the enactment of Law No. 6 of 2014 concerning the village. This study uses normative legal research in which data are collected and analyzed by the sentences associated with existing theories. The results of the study explained that the significance of the state recognizes indigenous villages namely to restore the identity and culture of rural communities, develop and preserve the local wisdom that a system of life of indigenous people of the village and as the controlling influence of globalization that destroys the social culture and Indonesian culture and restore the identity nation. Unification and pluralism to be one cause erosion of the power system and the character of the life of indigenous peoples through policies issued by the State. Therefore it is important to realize the concept of law that characterizes the character and culture of Indonesia in accordance with the times and the law in the society through the instrument of legislation.